Global, regional, and national trends in the burden of bipolar disorder among women of reproductive age from 1990 to 2021, and projections to 2041: a systematic analysis from the Global Burden of Disease Study 2021 - Hu, Feihu; Zhang, Huaichen; He, Qin; Zhang, Jing; Zhang, Jingbei; Song, Chuanfu; Yang, Cheng (Frontiers in Psychiatry, 2025)
BackgroundBipolar disorder (BD) is a severe mental illness characterized by alternating episodes of mania and depression. Among women of reproductive age (15–49 years), the risk of onset is higher and clinical manifestations are more complex due to the combined influence of hormonal fluctuations, reproductive pressures, and conflicts in social roles. Mental health problems in this population not only significantly impair quality of life but also place a sustained burden on family stability and public health systems. Although awareness of BD has been increasing, studies specifically focusing on the disease burden among women of reproductive age remain limited, particularly lacking systematic analyses based on the latest Global Burden of Disease (GBD) data.MethodsThis study was based on data from the GBD 2021 and systematically analyzed the incidence, prevalence, and disability-adjusted life years (DALYs) of BD among women aged 15–49 at the global, regional, and national levels from 1990 to 2021. We calculated age-standardized incidence rate (ASIR), prevalence rate (ASPR), and DALYs rate (ASDR), along with the estimated annual percentage change (EAPC) for each metric. In addition, cross-national health inequality was assessed using the slope index of inequality (SII) and the concentration index (CII). Future trends in the disease burden were projected to 2041 using a Bayesian age–period–cohort (BAPC) model.ResultsFrom 1990 to 2021, the overall burden of BD among women aged 15–49 years has continued to rise globally. In 2021, the numbers of new cases, prevalent cases, and DALYs were all significantly higher than in 1990. Although the ASIR showed a slight decline (EAPC = −0.07; 95% CI: −0.08 to −0.05), the ASPR and ASDR continued to increase, with EAPC of 0.06 (95% CI: 0.04–0.07) and 0.05 (95% CI: 0.04–0.07), respectively. High-SDI regions ranked highest across all three metrics, while middle-high SDI regions had the lowest ASIR and ASPR, and middle-low SDI regions had the lowest ASDR. Regionally, South Asia bore the heaviest absolute burden in terms of incident cases, prevalence, and DALYs, whereas Oceania had the lightest burden. In terms of standardized rates, Tropical Latin America had the highest ASIR, while Australasia recorded the highest ASPR and ASDR; East Asia had the lowest values across all three indicators. At the national level in 2021, New Zealand reported the highest ASIR, ASPR, and ASDR globally; China had the lowest ASIR, and the Democratic People’s Republic of Korea had the lowest ASPR and ASDR. The burden of BD was positively correlated with the level of socio-demographic development, showing a mild positive correlation between ASIR and SDI, and a stronger correlation for ASPR and ASDR. Age-wise, all age groups saw increases in incident cases, prevalence, and DALYs compared to 1990, with the 35–39 age group showing the greatest rise in incidence, and the 45–49 group the largest increase in prevalence and DALYs. In 2021, the ASIR peaked in the 15–19 age group, while ASPR and ASDR were highest in the 25–29 age group. Health inequality analysis indicated persistent disparities in BD burden between high- and low-SDI countries, with little improvement over the past three decades. Projections using the BAPC model suggest that ASIR, ASPR, and ASDR may slightly decline by 2041, but the overall disease burden is expected to remain high.ConclusionFrom 1990 to 2021, the disease burden of BD among women of reproductive age has continued to rise globally, exhibiting significant regional, national, and socioeconomic disparities. This highlights the uneven development of mental health systems across different settings. Countries should develop more targeted mental health intervention strategies based on their stage of development. It is recommended to strengthen early screening, standardized diagnosis, and long-term comprehensive management for women of reproductive age, in order to effectively reduce the disease burden and improve overall mental health in this population.